Development, modeling, and experimental investigation of low frequency workpiece vibration-assisted micro-EDM of tungsten carbide - Jahan, M. P. (American Society of Mechanical Engineers (ASME), 2010)
This present study intends to investigate the feasibility of drilling deep microholes in difficult-to-cut tungsten carbide by means of low frequency workpiece vibration-assisted micro–electrodischarge machining (micro-EDM). A vibration device has been designed and developed in which the workpiece is subjected to vibration of up to a frequency of 1 kHz and an amplitude of 2.5 m. An analytical approach is presented to explain the mechanism of workpiece vibration-assisted micro-EDM and how workpiece vibration improves the performance of micro-EDM drilling. The reasons for improving the overall flushing conditions are explained in terms of the behavior of debris in a vibrating workpiece, change in gap distance, and dielectric fluid pressure in the gap during vibration-assisted micro-EDM. In addition, the effects of vibration frequency, amplitude, and electrical parameters on the machining performance, as well as surface quality and accuracy of the microholes have been investigated. It has been found that the overall machining performance improves considerably with significant reduction of machining time, increase in MRR, and decrease in EWR. The improved flushing conditions, increased discharge ratio, and reduced percentage of ineffective pulses are found to be the contributing factors for improved performance of the vibration-assisted micro-EDM of tungsten carbide.